Hubungan Pengetahuan dengan Kemampuan Keluarga dalam Merawat Stroke - Aprina Aprina; Titi Astuti (Malahayati Nursing Journal, 2024)
ABSTRACTIntroduction: The prevalence of stroke in Lampung Province is 8.3%. Stroke patients who experience disability will lose their independence and become very dependent on other people. The role of the family is very important in helping patients meet their needs. The family's ability to care for patients is related to the theory of health behavior, namely knowledge, attitudes and actions. Purpose: This study aims to determine the relationship between knowledge and family ability in caring for stroke patients in the Natar Community Health Center working areaMethod: This research is a type of quantitative research using a cross sectional design. The research subjects were stroke sufferers in the Natar health center area, with a population of 35 patients with a sampling technique using purposive sampling. The research was conducted in May 2024 in the area. Natar Community Health Center work. Data collection uses a questionnaire, data analysis uses the Chi Square TestResult: Research results: Most respondents with fairly good knowledge, namely 16 (45.7%), and most respondents with low ability to care for stroke patients, namely 22 (62.9%), statistical test results show that respondents with poor knowledge good and had a low ability to care for stroke patients as many as 7 (77.8%). From the results of data analysis, the result was a p value = 0.004. This figure shows that the p value is 0.05, meaning that there is a relationship between knowledge and the family's ability to care for stroke patients in the Natar Community Health Center working areaConclusion: There is a relationship between knowledge and the family's ability to care for stroke patients in the Natar Community Health Center working area (p = 0.004. The community health center should facilitate increasing family and patient knowledge by making leaflets about stroke prevention so that families can fill their time by reading leaflets so as to increase family knowledge in implement preventive measuresKeywords: Keywords : Ability, Knowledge, Stroke    ABSTRAK Pendahuluan: Prevelensi stroke di Provinsi Lampung menjadi 8.3% , Pasien Stroke yang mengalami kecacatan akan kehilangan kemandirian dan sangat tergantung pada orang lain. Peran serta keluarga sangat penting membantu pasien dalam memenuhi kebutuhan, Kemampuan keluarga dalam merawat pasien berkaitan dengan teori perilaku Kesehatan yaitu pengetahuan, sikap, dan tindakan Tujuan: Penelitian mengetahui Hubungan Pengetahuan Dengan Kemampuan Keluarga Dalam Merawat Pasien Stroke Di Wilayah Kerja Puskesmas Natar.Metode Penelitian: Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan desain Cross sectional, Subjek penelitiannya adalah penderita Stroke yang berada di wilayah puskesmas Natar, dengan jumlah Populasi sebanyak 35 pasien dengan tekhnik pengambilan sampel menggunakan Purposive sampling, penelitian di lakukan Pada bulan Mei 2024 di Wilayah Kerja Puskesmas Natar. Pengumpulan data menggunakan Kuesioner, analisis data menggunakan Uji Chi SquareHasil: Hasil penelitian Sebagian besar responden dengan Pengetahuan Cukup baik yaitu sebanyak 16 (45,7%), dan sebagian besar responden dengan Kemampuan merawat pasien stroke rendah yaitu sebanyak 22 (62,9%), Hasil uji statistic menunjukkan bahwa responden dengan Pengetahuan Kurang baik dan memiliku Kemampuan merawat pasien stroke rendah sebanyak 7 (77,8%), Dari hasil analisis data diperoleh hasil nilai p = 0,004. Angka tersebut menunjukkan bahwa nilai p 0,05, artinya Ada Hubungan Pengetahuan Dengan Kemampuan Keluarga Dalam Merawat Pasien Stroke Di Wilayah Kerja Puskesmas Natar.Kesimpulan: Ada Hubungan Pengetahuan Dengan Kemampuan Keluarga Dalam Merawat Pasien Stroke Di Wilayah Kerja Puskesmas Natar (p = 0,004. hendaknya pihak puskesmas memfasilitasi peningkatan pengetahuan keluarga dan pasien dengan membuatkan leaflet tentang pencegahan Stroke agar keluarga dapat mengisi waktu dengan membaca leaflet sehingga meningkatkan pengetahuan keluarga dalam mengaplikasikan upaya pencegahanKata kunci: Kemampuan, Pengetahuan, Stroke